Static and Dynamic Ultrasound Imaging to Visualize the Bladder, Bladder Neck, Urethra, and Pelvic Floor in Children with Daytime Incontinence - Schroeder, Rogier; de Mooij, Keetje; Groen, Luitzen; Dik, Pieter; Kuijper, Caroline; Klijn, Aart; de Jong, Tom (Frontiers in Pediatrics, 2017)
Daytime urinary incontinence is a major health care problem with children. The condition occurs in 15% of 4 and 5% of 9.5-year-olds. The process of achieving continence comes from an intrinsic interaction between anatomical and functional factors. Standardisation of terms as well as diagnostic and therapeutic abilities have been greatly improved by the efforts done by dedicated institutions as presented in existing literature. Nevertheless, ascertaining the cause of incontinence remains a challenging task. More (and novel) diagnostic tools to pinpoint the exact reason for incontinence need to be evaluated. After all, only the right diagnosis can lead to appropriate therapy or even surgery. Ultrasound (US) can be a highly useful additive to basic physical examination. Already it is the primary imaging tool in paediatric patients with urological problems. US for the lower urinary tract is a valuable and patient friendly alternative to investigation using röntgen. It is well tolerated, not expensive, widely available (especially since the recently introduced portable machine), not invasive and needs no radiation. In the diagnostics of patients with daytime incontinence it can be of great value. Transabdominal US shows determinants like bladder volume, post-void residual urine, inflow urine jet, detrusor wall thickness, bladder neck and the rectum diameter. Transperineal US accurately visualises the urethra, bladder neck, rectum and vagina. Besides static (anatomical) images, dynamic imaging when using transperineal US to determine functional parameters can be very insightful. This paper focuses on US imaging of the lower urinary tract for patients with daytime incontinence. It associates our clinical practice and current insights in literature. Furthermore, we provide a practical guidance on how to perform transabdominal and transperineal US imaging.